The Effectiveness of the Taklim Assembly of Baitul Mizan Serang Kalikajar, Kalikajar District Wonosobo Regency in Improving the Quality of Faith and Takwa - Affan, Untaji; Imron, Imron (Prosiding University Research Colloquium, 2021)
Islam is a perfect religion, its Shari’a regulates the entire system of human life to achieve a happy life in this world and in the hereafter. The perfection of Islamic teachings includes the fields of aqidah, sharia, morality and muamalah, so that with that perfection through the holy book the Qur’an is conveyed gradually and the people accept Islamic da’wah gradually. The treasures of Islam are so deep and broad that they need to be conveyed wisely and full of example. Majelis Taklim is one of the educational institutions in the community that was established from, by and for the community, to convey, teach, understand, practice Islamic teachings and provide examples. This activity is held continuously, so that people who already have religion, beliefs and customs can accept and practice the teachings of Islam. Therefore, the taklim assembly has different forms, seen from the participants, the time of implementation, the method, the material. By not denying the efforts of religious leaders and administrators of the Baitul Mizan mosque, Serang Village, Kalikajar Village, Kalikajar District, Wonosobo Regency, that the taklim assembly is faced with the condition of human resources that are less able to adapt to the needs of the target group so that the taklim assembly has not been maximized in an effort to increase faith and piety to Allah. . Judging from the readiness of human resources to accept change, and the use of existing media (mosques) to compete in goodness.